Metaanálisis de la prevalencia de Chlamydia trachomatis entre hombres y mujeres militares (2023)
Introduction: Chlamydia trachomatis is the first cause of sexually transmitted infections in the world. The risk groups are young adults and it is postulated that it is greater in the military and in women. However, the evidence is heterogeneous. Objectiv